Socioeconomic Resilience in Sri Lanka : Natural Disaster Poverty and Wellbeing Impact Assessment - Walsh, Brian; Hallegatte, Stephane (World Bank, Washington, DC, 2019)
Traditional risk assessments use asset losses as the main metric to measure the severity of a disaster. This paper proposes an expanded risk assessment based on a framework that adds socioeconomic resilience and uses wellbeing losses as the main measure of disaster severity. Using an agent-based model that represents explicitly the recovery and reconstruction process at the household level, this risk assessment provides new insights into disaster risks in Sri Lanka. The analysis indicates that regular flooding events can move tens of thousands of Sri Lankans into transient poverty at once, hindering the country's recent progress on poverty eradication and shared prosperity. As metrics of disaster impacts, poverty incidence and well-being losses facilitate quantification of the benefits of interventions like rapid post-disaster support and adaptive social protection systems. Such investments efficiently reduce wellbeing losses by making exposed and vulnerable populations more resilient. Nationally and on average, the bottom income quintile suffers only 7 percent of the total asset losses but 32 percent of the total wellbeing losses. Average annual wellbeing losses due to fluvial flooding in Sri Lanka are estimated at US$119 million per year, more than double the asset losses of US$78 million. Asset losses are reported to be highly concentrated in Colombo district, and wellbeing losses are more widely distributed throughout the country. Finally, the paper applies the socioeconomic resilience framework to a cost-benefit analysis of prospective adaptive social protection systems, based on enrollment in Samurdhi, the main social support system in Sri Lanka.